2010
DOI: 10.1177/0269881110367724
|View full text |Cite
|
Sign up to set email alerts
|

Prodynorphin gene deletion increased anxiety-like behaviours, impaired the anxiolytic effect of bromazepam and altered GABAA receptor subunits gene expression in the amygdala

Abstract: This study evaluated the role of prodynorphin gene in the regulation of anxiety and associated molecular mechanisms. Emotional responses were assessed using the light-dark test, elevated plus maze and social interaction tests in prodynorphin knockout and wild-type mice. Corticotrophin releasing factor and proopiomelanocortin gene expressions in the hypothalamus were evaluated after restraint stress using in situ hybridization. The anxiolytic efficacy of bromazepam and GABA(A) receptor subunits gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 79 publications
1
14
1
Order By: Relevance
“…It is also important to emphasize that the relationship between PDYN and different aspects of negative affect is complex and still requires further investigation. For example, although stress-induced aversion is established to be mediated by elevated dynorphin (41,42), a number of investigations have documented that animals lacking the Pdyn gene have enhanced anxiety behavior (43,44). Moreover, our study underscores the heterogeneity of PDYN expression even within discrete brain regions, suggesting different PDYN circuits could contribute to distinct behavioral components relevant to negative affect.…”
Section: Figurementioning
confidence: 56%
“…It is also important to emphasize that the relationship between PDYN and different aspects of negative affect is complex and still requires further investigation. For example, although stress-induced aversion is established to be mediated by elevated dynorphin (41,42), a number of investigations have documented that animals lacking the Pdyn gene have enhanced anxiety behavior (43,44). Moreover, our study underscores the heterogeneity of PDYN expression even within discrete brain regions, suggesting different PDYN circuits could contribute to distinct behavioral components relevant to negative affect.…”
Section: Figurementioning
confidence: 56%
“…Changes in GABA A receptor subunits expression induced by stress will then promote differential clustering of selective subunits conditioning the receptor activity and its participation in stress and anxiety [25,4246]. While the GABA A γ 2 subunit is essential for the synaptic clustering of the GABA A complex [39,41,47], anti-anxiety effects are commonly linked to receptors highly expressing the GABA A α 2 subunits [42,43,48]. …”
Section: Discussionmentioning
confidence: 99%
“…Kuzmin et al (2006) showed that big dynorphin, a prodynorphin-derived precursor peptide, induced anxiolytic-like behavior in mice in the EPM test [47] . Whereas, deletion of the prodynorphin gene increased anxiety-like behaviors in the EPM and light-dark tests [48] . Similarly, ablation of prodynorphin showed increased anxietylike behaviors in zero-maze and startle-response tests [49] .…”
Section: Rodent Models Of Anxietymentioning
confidence: 95%